EXPLORING THE PRACTICAL APPLICATION AND APPRAISAL OF THE 2013 ENGLISH CURRICULUM IN A STATE JUNIOR HIGH SCHOOL: A QUALITATIVE INVESTIGATION - Milyarni, Farrah Dina; Sofendi, Sofendi; Mirizon, Soni (English Review: Journal of English Education, 2023)
The constant enhancement of Indonesia’s educational curriculum is aimed at improving the overall quality of education. This research specifically investigates the application of the 2013 English Curriculum at a state yunior high school in Palembang, South Sumatra, Indonesia, utilizing a qualitative evaluative approach. The study, conducted at SMP Negeri 1 Palembang, involved two English teachers and eighth-grade students. The findings revealed that the English teachers adhered to standard content and government syllabi when developing lesson plans. Teaching methods and assessments also aligned with government policies. Additionally, factors such as teacher quality, resource accessibility, and community involvement were identified as potential influencers on curriculum effectiveness. Although the curriculum has evolved, evaluating the 2013 curriculum can provide valuable insights for future improvements in Indonesia’s educational curriculum.